Internet Addiction, Oral Health Practices, Clinical Outcomes, and Self-Perceived Oral Health in Young Saudi Adults. (11th August 2020) - Al-Ansari, Asim; El Tantawi, Maha; AlMadan, Nasser; Nazir, Muhammad; Gaffar, Balgis; Al-Khalifa, Khalifa; AlBaty, Ali
Abstract : The study assessed the relationship between Internet addiction and oral health practices and clinical outcomes and whether this was affected by oral health perception. In 2017, a cross-sectional study included university students in the Eastern Province of Saudi Arabia. Questionnaires assessed demographic background, oral health practices (consuming sugar, tobacco use, and oral hygiene), perceived oral health, and Internet addiction. Caries experience and gingivitis were assessed using the World Health Organization criteria. The multivariate general linear analysis assessed the relationship between dependent variables (oral health practices, DMFT, and gingivitis) and exposure (Internet addiction). Data were available for 919 participants, 75.4% females, mean age = 19.8 years, and 1.6% with significant Internet use problem. The mean percentage of teeth with gingivitis was 8.5% and mean DMFT was 2.9. Among those with good perception of oral health and compared with participants with significant Internet use problem, average Internet users had lower consumption of sugar and tobacco ( B = −6.52, P = 0.03 and B = −2.04, P = 0.03 ), better oral hygiene practices ( B = 2.07, P = 0.33 ), higher DMFT ( B = 2.53, P = 0.10 ), and lesser gingivitis ( B = −15.45, P = 0.06 ). Internet addiction was associated with negative oral health practices and poor clinical outcomes among young Saudis. Holistic health promotion approaches need to address the negative impact of Internet addiction on health and oral health status for this at-risk age group.